2011
DOI: 10.1080/11250003.2011.563248
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of wild red pandas in Fengtongzhai Nature Reserve, China

Abstract: To describe general patterns of activity in wild red pandas (Ailurus fulgens) we used radio-telemetry in the field from May 2002 to April 2003 in Fengtongzhai Nature Reserve, China. Our results indicated a circadian activity rate of 48.6% (±12.4), with two peaks at 700-1000 h and 1700-1800 h. The activity rhythm was characterized by frequent active periods interspersed with rests. Red pandas were more active during the day than at night, and crepuscular activity rates were intermediate. Activity rate was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…We observed red pandas on the ground on three occasions, while the balance of the sightings were in trees. When we attempted to catch a grounded animal, we had to approach them to make them climb a tree as has been done elsewhere [ 13 , 24 , 25 ]. In this study, we observed them fleeing some distance on the ground in front of the trackers before they climbed a tree.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We observed red pandas on the ground on three occasions, while the balance of the sightings were in trees. When we attempted to catch a grounded animal, we had to approach them to make them climb a tree as has been done elsewhere [ 13 , 24 , 25 ]. In this study, we observed them fleeing some distance on the ground in front of the trackers before they climbed a tree.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed them fleeing some distance on the ground in front of the trackers before they climbed a tree. In China, dogs have also been used to chase red pandas to make them climb a tree [ 24 ], but this seems an unacceptably stressful way to capture red pandas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations